AUTOMATING LEARNING PROCESSES USING ARTIFICIAL INTELLIGENCE AND DATA ANALYTICS - Saydullayeva Saodat Abdumajitovna; Yusupov Nurmuhammad Otabek o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article analyzes the possibilities of automating educational processes in the higher education system using artificial intelligence (AI) and data analysis. The role of AI technologies in increasing the effectiveness of education, adaptive learning systems, and forecast analysis are highlighted. Based on the Decree of the President of the Republic of Uzbekistan No. PP-5253, the development of digital educational platforms will also be considered. The study analyzed the advantages and possible problems of integrating AI technologies into the educational process and developed practical recommendations.